Short term outcome after left atrial appendage occlusion with the AMPLATZER Amulet and WATCHMAN device: results from the ORIGINAL registry (saxOnian RegIstry analyzinG and followINg left atrial Appendage cLosure) - Lucie Kretzler; Christoph Mues; Carsten Wunderlich; Anke Langbein; S. G. Spitzer; Ulrich Gerk; Sebastian Schellong; Thomas Ketteler; Hans Neuser; Marcus Schwefer; Ruth Strasser; Karim Ibrahim; et al. (BMC Cardiovascular Disorders, 2022)
Abstract Background Various randomized multicenter studies have shown that percutaneous left atrial appendage closure (LAAC) is not inferior in stroke prevention compared to vitamin K antagonists (VKA) and can be performed safely and effectively. Aims The prospective multicenter ORIGINAL registry in the Free State of Saxony (saxOnian RegIstry analyzinG and followINg left atrial Appendage cLosure) investigated the efficiency and safety of LAAC with Watchman or Amulet device in a real word setting. A special focus was put on the influence of LAAC frequency on periprocedural efficiency and safety. Methods and results The total of 482 consecutive patients (Abbott Amulet N = 93 and Boston Scientific Watchman N = 389) were included in the periinterventional analyses. After 6 weeks, 353 patients completed the first follow-up including transoesophageal echocardiography (TEE) (73.2%). Successful LAAC could be performed in more than 94%. The complication rate does not significantly differ between device types (p = 0.92) according to Fischer test and comprised 2.2% in the Amulet and 2.3% in the Watchman group. The kind of device and the frequency of LAAC per study center had no influence on the success and complication rates. Device related thrombus could be revealed more frequently in the Watchman group (4.5%) than in the Amulet group (1.4%) but this difference is still not significant in Fisher test (p = 0.14). Same conclusion can be made about residual leakage 1.1% versus 0% [not significant in Fisher test (p = 0.26)]. Dual antiplatelet therapy followed the intervention in 64% and 22% of patients were discharged under a combination of an anticoagulant (VKA/DOAC/Heparin) and one antiplatelet agent. Conclusions The ORIGINAL registry supports the thesis from large, randomized trials that LAAC can be performed with a very high procedural success rate in the everyday clinical routine irrespective of the used LAA device (Watchman or Amulet). The postprocedural antithrombotic strategy differs widely among the participating centers. Trial registration Name of the registry: "saxOnian RegIstry analyzinG and followINg left atrial Appendage cLosure", Trial registration number: DRKS00023803; Date of registration: 15/12/2020 'Retrospectively registered'; URL of trial registry record: https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00023803 .